Intraoperative acute compartment syndrome of the upper limb secondary to extravasation. Issue 5 (17th May 2022) - Ang, Andrew; Michaelides, Athena; Hallworth, Stephen; Kocher, Hemant M
Abstract : A woman in her 50s was undergoing a repeat liver resection surgery for recurrence of liver metastasis when the intravenous fluid flow was noted to be sluggish on multiple occasions. On the third examination of the right hand where the intravenous cannula was located, surgery was halted as there was extensive swelling from the hand to the biceps and the hand had started turning blue. A diagnosis of acute upper limb compartment syndrome secondary to extravasation exacerbated by metaraminol was made by the anaesthetist and surgeon. Fasciotomies of the right upper limb were performed, and perfusion was restored. A hand surgeon arrived shortly after and completed decompressing the upper limb compartments. A literature review revealed risk factors such as communication barriers, age and chemotherapy were present in this case. Enhanced monitoring is needed in the context of unsatisfactory infusion flow rates perioperatively.